Anjuran Bertaubat dalam Hadis Nabi Saw. dan Implementasinya di Era Modern - Abdullah; Halimatussadiyah; Sulaiman M. Nur (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
Repentance is an important teaching in Islam, serving as a means of cleansing oneself from sin and as a form of a Muslim's devotion to Allah SWT. The hadiths of the Prophet Muhammad (peace be upon him) explicitly encourage Muslims to constantly repent, regardless of the magnitude of the sin committed. This article aims to examine the concept of repentance in the hadiths of the Prophet (peace be upon him) and analyze its implementation in the lives of Muslim communities in the modern era. This research uses a descriptive-qualitative method with a library research approach to thematic hadiths on repentance relevant to contemporary issues.The results show that repentance, from the perspective of the hadith, encompasses three main elements: regret for sin, cessation of sinful behavior, and a strong commitment not to repeat it. Implementation of the value of repentance in the modern era can be realized through self-control in the use of technology, increased spiritual awareness, and the development of ethical social behavior amidst challenges such as pornography, promiscuity, neglect of worship, backbiting, and slander. This study concludes that the teaching of repentance.